The Effectiveness of Climate-smart Agriculture Practices in Coffee Production at Dlie Ya Commune in Dak Lak Province - Nhung, Doan Thi; Anh, Dao The; Hai, Nguyen Thi; - Ishiwata, Yuki Ishikawa; Thi Hoang Ha, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
This study aimed to quantitatively assess the effectiveness of climate-smart agriculture (CSA) practices in coffee production in Dlie Ya commune, Dak Lak province. A theme-based framework and an indicator-based method with 23 indicators of five components (beneficiaries and yield, enabling environment, natural resources, emission, and benefits and welfare) were used. Semi-structured interviews with 107 local households were conducted. Data were coded, normalized to a 0-1 scale, and assessed, of which 1 refers to the highest effectiveness of CSA practices. Intercropping and soil coverage (mulching) were the two most common CSA practices in the study area. The CSA practices of intercropping and soil cover showed several advantages over not using these practices. These benefits included increased coffee yield, more stable yield variability, and reduced use of natural resources. The effectiveness score for intercropping was 0.66, significantly higher than the score for no intercropping (0.61) ( p < 0.001). Soil coverage had an effectiveness score of 0.68, which was higher than no soil coverage (0.60) ( p < 0.001). The results of this study indicate that intercropping and soil cover are good CSA practices and should be promoted for broader adoption among coffee farmers. Despite the results showing higher yields with the introduction of CSA, farmers still need to consider comprehensive measures to make their decisions. Training workshops organized by the local government might be essential to communicate the benefits of CSA practices to local farmers. Keywords: climate-smart agriculture, coffee, effectiveness, indicator, Vietnam .